Expression of parathyroidlike protein in normal, proliferative, and neoplastic human breast tissues. - Liapis, H. (1993)
Parathyroidlike peptide (PLP), or parathyroid hormone-related protein, is a protein of uncertain biological function that is structurally homologous to parathyroid hormone. Immunohistochemical studies have identified aminoterminal epitopes of PLP in breast carcinomas, but not in normal breast. In the present studies, immunohistochemistry and in situ hybridization were performed to evaluate further expression of PLP in normal, proliferative, and neoplastic breast tissues. Using a polyclonal antibody that recognizes epitopes within the middle and carboxyl-terminal domains of PLP, immunoreactive protein was detected within the cytoplasm of lobular and ductal epithelial cells in all normal and fibrocystic breast tissues from 74 patients. The intensity of cytoplasmic staining was increased in association with lactation, adenosis, and simple or atypical ductal hyperplasia and decreased in atrophic lobules. Cytoplasmic reactivity was also observed in 69% (56 of 81) of breast adenocarcinomas. Expression of immunoreactive PLP was inversely correlated with tumor stage and extent of nodal involvement at the time of diagnosis. However, there was no significant correlation with tumor grade, patient age, or hormone receptor status. In situ hybridization studies confirmed the epithelial expression of PLP messenger RNA in PLP-positive normal and neoplastic breast tissue. Interestingly, tumor-associated calcifications were identified in 43% of PLP-positive carcinomas, but in only 12% of PLP-negative carcinomas (P < 0.007). Our results suggest that PLP plays some role in the normal differentiated function of mammary epithelial cells and are consistent with the hypothesis that expression of this protein influences local calcium metabolism.